Otomycosis In The Fishermen Community: A Survey At Bénisaf Harbour, Aïn Témouchent, Algeria - Merad, Yassine; Adjmi-Hamoudi, Haiet; Samia Merad, Fatima Zohra; Djeriou, Souad (Journal of Medical Biomedical and Applied Sciences, 2018)
Otomycosis, is called âswimmers earâ, it is a common ear disease in moist environment.The aim of this survey was to detect otomycosis among the fishing community of BÃ©nisaf harbour, Ain-TÃ©mouchent (Algeria). The study involved 220 artisanal fishermen, 18 specimens of ear swabs, and ear scrapings from individuals with clinical otitis were examined from June to August 2015. These specimens were submitted for mycological investigation for reasons such as pruritus, ear blocking or tinnitus. Prevalence of otomycoses among fishermen with otitis was 38,9% (7 positive cases). The maximum of positive patients was seen in the age group above 41 years (57,1%), and 57,1% of positive cases had over 21 yearsâ experience of working as a fisherman. Candida genus was the most encountered fungi (57,14%), followed by moulds (42,58%). Fishermen work in aquatic environment and are exposed to heat and moisture.In summary, this study demonstrates that the diagnosis of otomycoses among fishermen requires vigilance from clinician given its non-specific symptoms.